Peluang Program Studi Akuntansi Bisnis Digital di Kalimantan Timur: Sebuah Survei - Kusumawati, Ratna Dewi; Kusno, Hendra Sanjaya; Apriani, Endang Sri; Dewi, Made Lia Ananda; Ramadhani, Ranita (SAFE-Network, 2025)
This survey-study aims to provide an overview of the interest in higher education among high school students in Akuntansi Bisnis Digital programs, in East Kalimantan, and to map the needs of industrial world needs related to graduates with digital business accounting skills in East Kalimantan. The data for this study were obtained through the distribution of questionnaires to high school students for the study interest survey and to industrial companies for the industry needs survey. The samples taken for this survey were high school students in East Kalimantan and companies in the East Kalimantan region. The data were then processed simply to interpret the results. The survey results showed that respondents with interest in studying had the intention to continue their studies to a higher education, and specifically, 56% of respondents were interested in continuing their studies to Akuntansi Bisnis Digital study program. Furthermore, the survey results for industry needs stated that 97% of industries require workers with digital business accounting knowledge, where these workers understand accounting and business as well as related technologies, where these skills can be obtained from graduates of the digital business accounting study program.